Enzyme Mimics: A Novel AuNP‐Based Glucose Oxidase Mimic with Enhanced Activity and Selectivity Constructed by Molecular Imprinting and O2‐Containing Nanoemulsion Embedding (Adv. Mater. Interfaces 22/2018). Issue 22 (22nd November 2018) - Fan, Lin; Lou, Doudou; Wu, Haoan; Zhang, Xizhi; Zhu, Yefei; Gu, Ning; Zhang, Yu
Abstract : A gold nanoparticle (AuNP)‐based mimic enzyme with selectivity and applicability in practical glucose detection of drinks and blood glucose is constructed by combining adjacent hydroxyls‐bindable aminophenylboronic acid and molecular imprinting technology, which also lead to a 270‐fold enhanced catalytic efficiency ( k cat / K m ) by increasing the affinity to substrate and introducing heptadecafluoro‐ n ‐octyl bromide nanoemulsion as an oxygen donor at the same time. More details can be found in article number1801070 by Lin Fan, Yu Zhang, and co‐workers.